Languages of Science between Western and Eastern Civilizations (De Gruyter, 2024)
In this volume, specialists in various fields of cultural studies investigate the ways in which scientific knowledge was transferred and disseminated throughout Eurasia between the 17th and 19th centuries. The papers highlight the intellectual effort and strategies by which scientific works were made available and understandable to audiences whose cultural background was very different from that for which they had been originally created.